Loose-part media and pictures on environmental themes increase interest in early childhood learning - Siti Shalichah; Santoso; Muchammmad Widjanarko (Universitas Pendidikan Ganesha, 2022)
Children experience difficulties in learning at school and a lack of interest in children during the learning process. Teachers and parents need to be made aware of this. They think this is because children are lazy when studying. This study analyzed loose part media and pictures on environmental themes to increase interest in early childhood learning. This research method uses quantitative methods with steps to formulate problems, determine the theoretical basis, formulate hypotheses, collect data, conduct data analysis, and draw conclusions. The analysis used in this research is quantitative and qualitative. Includes using loose part media and images, learning observations, and product validation of loose parts media and images. Analysis of loose part media and images to increase interest in early childhood learning includes six stages. The results showed a significant effect of the application of loose part media on environmental themes on children's learning interest based on a t count of 17,812 and a t table of 1.9977, so the t count is more than the t table. The application of environmental theme image media significantly affects children's learning interests with a t table of 1.9995. There is a significant influence of the application of environmental theme loose part media and environmental theme image media on children's learning interest with a t count of 14,483 and a t table of 1.9939. The conclusion is that there is a significant influence of the application of environmental theme loose part media and environmental theme image media on the learning interest of group B students.